Basic Profile of the Child Marriage in Guinea - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
This brief has provided a basic profile of child marriage in Guinea. Measures of child marriage are high. The share of women ages 18-22 who married as children is 51.1 percent, but it has declined over time, but not dramatically so. The share of girls marrying very early, before the ageof 15, has also declined, but not very rapidly either. Child marriage is associated with lower wealth, lower education levels, and higher labor force participation. These are however only correlations, not necessarily causal effects. Other briefs in this series look at potential causal effects.